EVALUASI PEMBELAJARAN BAHASA ARAB KELAS 7 DI MARHALAH SALAFIYAH WUSTHO PONDOK PESANTREN ISLAMIC CENTRE BIN BAZ PUTRI YOGYAKARTA - Umareni; Unaisah Soehardin; Eko Ngabdul Shodikin (ASCENT: Al-Bahjah Journal of Islamic Education Management, 2024)
Arabic is a mandatory language that cannot be separated from Islamic boarding schools, which is like two sides of a coin because it is the language of the Islamic religion. It will be easier for students to understand the Qur'an or the books they are studying if they master Arabic. Good learning of Arabic must be accompanied by evaluation so that it is clear what things support and hinder it. Evaluation includes four types of proficiency and skill tests (maharah), namely listening (istima'), speaking (kalam), reading (Qiro'ah), and writing (Kitabah). The research aims to determine the evaluation of Arabic language learning at the Islamic Center Bin Baz Islamic Boarding School (ICBB) Putri Yogyakarta, especially grade 7 Salafiyah Wustho. This research uses a qualitative-descriptive approach and aims to find out how language is practiced at the Bin Baz Putri Islamic Center Islamic Boarding School. The results of the study showed different levels of proficiency in the four language skills (listening, speaking, reading, and writing), namely Kitabah proficiency, which showed the highest achievement of 90%, Qiro'ah proficiency (85%), Istima' proficiency (85%), and Kalam proficiency (80%).